2020
DOI: 10.1136/jnnp-2019-322042
|View full text |Cite|
|
Sign up to set email alerts
|

Brain iron deposition is linked with cognitive severity in Parkinson’s disease

Abstract: BackgroundDementia is common in Parkinson’s disease (PD) but measures that track cognitive change in PD are lacking. Brain tissue iron accumulates with age and co-localises with pathological proteins linked to PD dementia such as amyloid. We used quantitative susceptibility mapping (QSM) to detect changes related to cognitive change in PD.MethodsWe assessed 100 patients with early-stage to mid-stage PD, and 37 age-matched controls using the Montreal Cognitive Assessment (MoCA), a validated clinical algorithm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 67 publications
9
135
0
1
Order By: Relevance
“…Higher iron in CN predicted lower dementia rating scale score (r = -0.7, p = 0.0232; Rho = -0.56, p = 0.0944); Lower arithmetic score correlated higher iron in CN (r = −0.64, p = 0.0481; Rho = −0.70, p = 0.0359) and putamen (r = −0.78, p = 0.0077; Rho = −0.65, p = 0.0495); TH iron was predictive of Digit Symbol output (r = 0.77, p = 0.0088; Rho = 0.57, p = 0.0865), time taken to complete the test (r = −0.79, p = 0.0069; Rho = −0.56, p = 0.0909), and MMSE scores (r = 0.66, p = 0.0397; Rho = 0.47, p = 0.1611); In the two choice test CN iron correlated with longer reaction time by the left (r = 0.56, p = 0.0918) and right (r = 0.79, p = 0.0062) hands, higher GP iron correlated with longer reaction time by the right hand (r = 0.65, p = 0.0421) and higher PU iron correlated with longer movement time by the left (r = 0.70, p = 0.024) hand; Fine finger movement speed showed no significant relationship with iron estimates in any region; In the Digit Symbol grid, CN and TH iron accounted for 80% of the variance; Low TH iron (p = 0.0096) was a unique predictor of performance over the caudate iron measure (p = 0.5192) Sun et al, 2017 [61] svMCI group had significantly lower composite, attention-executive, memory and language z scores than controls; significantly higher susceptibility in svMCI group over controls in R-HP (p<0.01), L-HP (p<0.01), R-PU (p<0.05); svMCI group had significantly negative correlation between sus in R-HP and memory z sore (p = 0.012); susceptibility in R-HP of svMCI group was positively correlated to language z score (p = 0.026); susceptibility in R-PU in the svMCI group was significantly negatively correlated to attention-executive z score (p = 0.033); composite z score not related to susceptibility Thomas et al, 2020 [62] Increase in QSM in PD compared to controls in prefrontal cortex, R-PU and Rtemporal cortex (p<0.05); Increased QSM in SN in PD compared to controls (p = 0.004); In PD patients there was susceptibility increase with decreasing MoCA scores in HP, TH, CN, caudal regions of ventromedial prefrontal cortex, regions of basal forebrain, R-PU and R-insular cortex; Increased absolute susceptibility with increased dementia risk score in PD patients (p<0.05); widespread QSM increases in patients with poor visual performance (p<0.05); PD group showed significant increase in susceptibility (p<0.05) with UPDRS-III in right PU…”
Section: Sullivan Et Al 2009 [60]mentioning
confidence: 96%
“…Higher iron in CN predicted lower dementia rating scale score (r = -0.7, p = 0.0232; Rho = -0.56, p = 0.0944); Lower arithmetic score correlated higher iron in CN (r = −0.64, p = 0.0481; Rho = −0.70, p = 0.0359) and putamen (r = −0.78, p = 0.0077; Rho = −0.65, p = 0.0495); TH iron was predictive of Digit Symbol output (r = 0.77, p = 0.0088; Rho = 0.57, p = 0.0865), time taken to complete the test (r = −0.79, p = 0.0069; Rho = −0.56, p = 0.0909), and MMSE scores (r = 0.66, p = 0.0397; Rho = 0.47, p = 0.1611); In the two choice test CN iron correlated with longer reaction time by the left (r = 0.56, p = 0.0918) and right (r = 0.79, p = 0.0062) hands, higher GP iron correlated with longer reaction time by the right hand (r = 0.65, p = 0.0421) and higher PU iron correlated with longer movement time by the left (r = 0.70, p = 0.024) hand; Fine finger movement speed showed no significant relationship with iron estimates in any region; In the Digit Symbol grid, CN and TH iron accounted for 80% of the variance; Low TH iron (p = 0.0096) was a unique predictor of performance over the caudate iron measure (p = 0.5192) Sun et al, 2017 [61] svMCI group had significantly lower composite, attention-executive, memory and language z scores than controls; significantly higher susceptibility in svMCI group over controls in R-HP (p<0.01), L-HP (p<0.01), R-PU (p<0.05); svMCI group had significantly negative correlation between sus in R-HP and memory z sore (p = 0.012); susceptibility in R-HP of svMCI group was positively correlated to language z score (p = 0.026); susceptibility in R-PU in the svMCI group was significantly negatively correlated to attention-executive z score (p = 0.033); composite z score not related to susceptibility Thomas et al, 2020 [62] Increase in QSM in PD compared to controls in prefrontal cortex, R-PU and Rtemporal cortex (p<0.05); Increased QSM in SN in PD compared to controls (p = 0.004); In PD patients there was susceptibility increase with decreasing MoCA scores in HP, TH, CN, caudal regions of ventromedial prefrontal cortex, regions of basal forebrain, R-PU and R-insular cortex; Increased absolute susceptibility with increased dementia risk score in PD patients (p<0.05); widespread QSM increases in patients with poor visual performance (p<0.05); PD group showed significant increase in susceptibility (p<0.05) with UPDRS-III in right PU…”
Section: Sullivan Et Al 2009 [60]mentioning
confidence: 96%
“…Recently, various neuroimaging studies are focusing on PD-MCI to examine which type of pathology is a dominant cause of cognitive impairment. Some studies using quantitative susceptibility mapping have indicated that brain iron deposition is linked with cognitive severity in PD [22,23]. Thomas Herein, we discuss about the deactivation of the MFG and IPL.…”
Section: Discussionmentioning
confidence: 97%
“…This technique is sensitive to iron, calcium and other magnetic substances [ 80 ]. The deposition of iron measured using QSM has been linked with cognition in Alzheimer’s disease [ 81 ] and Parkinson’s disease [ 82 ]. In Alzheimer’s disease, iron is found in the plaques and tangles that characterise the disease, though there is still some work required to establish what exactly is being identified, for example whether ferrous or ferric iron is picked up by QSM.…”
Section: The Next Big Thing…?mentioning
confidence: 99%